ILIOPSOAS IMPINGEMENT AFTER TOTAL HIP ARTHROPLASTY - FINITE ELEMENT ANALYSIS - Pop, Sorin Tudor; Zuh, Sandor-Gyorgy; Hidi, Margit; Vass, Attila; Gergely, Istvan (European Scientific Journal, ESJ, 2015)
Aim of this paper. Is to study the iliopsoas impingement with threedimensional modeling (3D) after total hip arthroplasty in extended position of the hip in case of 28 and 36 mm diameter prosthetic heads and the acetabular component in malposition (retroversion). Material and methods. We performed a 3D reconstruction of the pelvic bone, the left femur and left iliopsoas muscle of a 27 year old male based on CT images. After that we created a solid body that we used for the arthroplasty performed in the variants mentioned above and we used the finite element method for the analyses. Results. There were no traces of impingement with the 28 mm and 36 mm diameter femoral head, when the joint is in extension. When the acetabular component was in malposition, we found a stress aerie on the iliopsoas muscle and acetabular component meeting point. Conclusion. In our research, we demonstrated by 3D modeling and finite element analysis that after total hip arthroplasty using a large diameter femoral head, with the hip in extension, there is no pressure on the surface of iliopsoas muscle, contrary with the case of the acetabular component in retroversion. We can avoid this placing the acetabular component in angle of 45o inclination and 10o anteversion.